STRATEGI PENINGKATAN MUTU LULUSAN DALAM MENGHADAPI TANTANGAN DAN ISU GLOBAL (STUDI KASUS STISIP TASIKMALAYA) - Aziz, Nur; Muslim, Khidayat; Ilmi, Irpan (MPI STAI Sangatta Kutai Timur, 2024)
This study aims to analyze the strategy of improving the quality of graduates at STISIP Tasikmalaya in facing the challenges of globalization. The importance of this research lies in addressing the gap in the literature regarding comprehensive strategies that integrate curriculum development, soft skills enhancement, and industry collaboration holistically, especially in the context of local universities. This research used a qualitative approach with a case study method, which involved in-depth interviews, participatory observation, and documentation. Data were analyzed using the Miles and Huberman model through the stages of data condensation, data presentation, and conclusion drawing and verification. The results showed that STISIP Tasikmalaya's strategies, such as strengthening competency-based curriculum, soft skills training, and internship programs, have improved graduates' readiness to face global challenges. This strategy is proven effective through tracer study data which shows that 90% of graduates get jobs in less than six months. However, the institution still faces obstacles such as limited resources and regional competition. This research has implications for the development of a strategic framework for other universities in responding to global dynamics, as well as providing guidance for creating competitive and adaptive graduates.